Evaluasi Sistem Proteksi Hidrant sebagai Pengendalian Bahaya Kebakaran Pada Bangunan Perkantoran dengan Luas Bangunan 35.190 m2 - Al Qadry; A B Pratama; J F HT Saragi; F TH Sinaga; E P D Boangmanalu (Jurnal MESIL (Mesin Elektro Sipil), 2023)
In general, every building must be protected from fire hazards by passive and active fire protection systems. The application of a passive or active protection system is based on the function/classification, area, height, volume, building materials installed, and/or the number of building occupants. Therefore, we need a fire prevention system to reduce the impact and losses caused by fires. Fire Protection Systems are generally regulated by Permen PU 26/PRT/M/2008 concerning Technical Requirements for Fire Protection Systems in Buildings and the Environment, and then these requirements are grouped according to their respective aspects including, Hydrant Systems, pipe systems upright, Sprinkler System, and Smoke control system. The Hydrant Pump consists of Joekey 25 GPM, Electric and Diesel with a capacity of 1000 GPM